2020
DOI: 10.18280/ijsdp.150707
|View full text |Cite
|
Sign up to set email alerts
|

New Holistic Strategy of Sustainable Rural Development Management-Experience from Indonesia: A PESTEL-SOAR Analysis

Abstract: This article offers a new strategy of holistic rural development by utilizing the external strengths of the rural and the internal strength based on the experience of one of the rural in Indonesia that has been succeeded in turning the rural from the poorest into the best in the national rank. The successful formula is associated with the role of village leaders in benefiting opportunities from the existing external-internal aspects. To capture more holistic development phenomena including political, economic,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 9 publications
0
5
0
1
Order By: Relevance
“…Data yang sudah dikumpulkan selanjutnya dianalisis guna membahas strength (kekuatan), opportunity (peluang), aspirations (aspirasi), dan result (hasil) yang disajikan dalam bentuk tabel SOAR (Muhardi et al 2020;Rashidi et al 2017).…”
Section: Metodeunclassified
“…Data yang sudah dikumpulkan selanjutnya dianalisis guna membahas strength (kekuatan), opportunity (peluang), aspirations (aspirasi), dan result (hasil) yang disajikan dalam bentuk tabel SOAR (Muhardi et al 2020;Rashidi et al 2017).…”
Section: Metodeunclassified
“…It does so by directing attention toward existing strengths (with a focus on strengths and opportunities in the present) and envisioning future outcomes (centering aspirations and results for the future). Notably, SOAR analysis has witnessed a substantial increase in its application within the context of formulating strategies and action plans for sustainable tourism development [123][124][125][126].…”
Section: Methodsmentioning
confidence: 99%
“…Based on the identification of the variables/attributes that determine the sustainability of village development in the Bukit Rimbang Bukit Baling Wildlife Reserve area in Kampar Regency, 15 variables/attributes have been found that have leverage. These variables/attributes include (1) amenity resources, (2) village community awareness of the environment, (3) population emigration, (4) culture and education, (5) community empowerment, (6) level of village community financial literacy, (7) village electrification, (8) the role of BUMDesa and BUMDesa Bersama, (9) basic service facilities and infrastructure, (10) village connectivity, (11) utilization of communication tools and the internet, (12) land cases, (13) government commitment to financing village development, (14) policies to minimize land conversion, and (15) integration and synergy of village development. Furthermore, based on these variables, a participatory prospective analysis was carried out involving village development stakeholders in the Bukit Rimbang Bukit Baling Wildlife Reserve area in Kampar Regency which resulted in an agreement that the dominant variables that have influence and dependency in increasing village development include (1) Village connectivity, (2) Basic service facilities and infrastructure, (3) community empowerment, (4) Amenity resources, (5) integration and synergy of village development.…”
Section: Discussionmentioning
confidence: 99%
“…The sense of togetherness, kinship, and cooperation that is still strong in the village community is a source of local wisdom for village development [7]. The village's internal and external potentials and opportunities must be managed holistically [8].…”
Section: Introductionmentioning
confidence: 99%